2019
DOI: 10.1080/1547691x.2019.1657993
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to low-dose arsenic in early life alters innate immune function in children

Abstract: Early-life exposure to arsenic (As) increases risks of respiratory diseases/infections in children. However, data on the ability of the innate immune system to combat bacterial infections in the respiratory tracts of As-exposed children are scarce. To evaluate whether persistent low-dose As exposure alters innate immune function among children younger than 5 years-of-age, mothers and participating children (N ¼ 51) that were members of the Health Effects of Arsenic Longitudinal Study (HEALS) cohort in rural Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In parallel with impaired lymphocyte functioning, As toxicity is also associated with chronic inflammation and reduced phagocytic receptors—Fcγ and complement receptors (CR) ( Prasad, Sinha, 2017 ). Correspondingly, As exposure was shown to affect innate immunity factors in children ( Parvez et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with impaired lymphocyte functioning, As toxicity is also associated with chronic inflammation and reduced phagocytic receptors—Fcγ and complement receptors (CR) ( Prasad, Sinha, 2017 ). Correspondingly, As exposure was shown to affect innate immunity factors in children ( Parvez et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying mechanisms needed to be clarified in future studies. Additionally, urinary arsenic levels were seen to be negatively associated with peripheral blood mononuclear cell formation of fractalkine and IL-7, and positively associated with that for IL-13, IL-17 and MIP-1 α in children [ 38 ], suggesting the associations may existed for urinary arsenic with perturbations of inflammatory processes in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is the monomethyl metabolite of arsenite (MMA +3 ) that seems to be responsible for suppression of TCP [ 37 ]. In human studies, As exposure has been associated with alterations in immune function, including suppression of innate and adaptive immunity [ 41 , 42 ], perhaps leading to increased cancer [ 43 ], and increased upper airway infections [ 44 ]. Our studies have shown that As can elevate IL-1β [ 14 ], suggesting that As exposure induces a proinflammatory state.…”
Section: Discussionmentioning
confidence: 99%